The Effect of Tangram Media on the Learning Outcomes of Class V Mathematics Subjects in Elementary Schools - Maslachatul Choiroh (Universitas Muhammadiyah Sidoarjo, 2018)
This research is motivated by demands in the development of the learning process. Student learning outcomes are redAnalyzing the influence of tangram media on student learning outcomes on mathematics subjects in 5rd students of Suced because the media used is less attractive in the learning process. Use of this tangram media, in order to have an impact on learning outcomes that are better than usual, especially in the material Identifying Flat Build Properties. Simo Angin-Angin Elementary School and to determine the influence of tangram media on student learning outcomes on mathematics subjects in class 5rd of Simo Angin-Angin Elementary School is a goal that researchers formulate. this was carried out at Simo Angin-Angin Elementary School, Wonoayu District. The researcher used quantitative research using Pre Experimental Design. With the design form of One Group Pretest-Posttest Design. The effect of tangram media on student learning outcomes can be analyzed from the analysis of relative value distribution and N-Gain. The research subjects were 20 students. Data were analyzed through pretest and posttest. Obtained results of N-Gain 0.72, it can be concluded that the tangram media has a high interpretation, so that from the test of the relative value distribution there is the influence of tangram media on student learning outcomes. From the N-Gain analysis the results of the value of 0.72 showed that the results of the high influence between tangram media on student learning outcomes.